3-3-1 models at electroweak scale - Dias, A. G.; Montero, J. C. [UNESP]; Pleitez, V. [UNESP] (Elsevier B.V., 2006)
We show that in 3-3-1 models there exist a natural relation among the SU(3)(L) coupling constant g, the electroweak mixing angle theta(W), the mass of the W, and one of the vacuum expectation values, which implies that those models can be realized at low energy scales and, in particular, even at the electroweak scale. So that, being that symmetries realized in Nature, new physics may be really just around the corner. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 3-3-1 model; neutral currents